STUDI TERHADAP BANK BRI SYARIAH CABANG KEDIRI: AKAD MURABAHAH DALAM KEPEMILIKAN PERUMAHAN RAKYAT (KPR) - Riza Taufiqi Majid; Imam Thoha; Mualifah (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2023)
The aim of this research is to ascertain the implementation and mechanism of murabahah contract in the People's Housing Ownership Scheme (KPR) and to identify the challenges encountered when applying the murabahah contract in the iB BRI Syariah KPR scheme. This study employs a qualitative method. This approach views social reality as holistic (comprehensive, inseparable), complex, dynamic, full of meaning, and characterized by interactive relationships (reciprocal). In analyzing the data, the author identifies themes and formulates hypotheses (ideas) presented by the data, as well as endeavors to demonstrate that these themes and hypotheses are supported by the data. The hypotheses written by the researcher merely seek to demonstrate that the hypotheses proposed are logical or obtain logical understanding consistent with the researched theme.